1998
DOI: 10.1021/la980890k
|View full text |Cite
|
Sign up to set email alerts
|

Binding of Aromatic Anions to Cetylpyridinium Aggregates Either Adsorbed at Silica/Water, Alumina/Water, Titanium Dioxide/Water Interfaces or in Solution

Abstract: The influence of the counterions on the adsorption properties of cetylpyridinium salicylate, cetylpyridinium 4-aminosalicylate, cetylpyridinium 5-aminosalicylate, and cetylpyridinium chloride has been investigated at silica/water interfaces using adsorption isotherm determinations and electrophoretic and surface tension measurements. Earlier results are confirmed which showed that replacing the chloride ion by the salicylate ion results in a 6-fold increase in the plateau value of the surfactant ion. It is sug… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
13
0

Year Published

2001
2001
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(17 citation statements)
references
References 36 publications
4
13
0
Order By: Relevance
“…With an increase in r , the Γ m increases, while Γ m g decreases, which is consistent with the prediction of our size-effect model. The Γ m values for the four silica samples at pH 9.00 are in the range of 4.18–6.28 μmol/m 2 , similar to the previous reports. Furthermore, with an increase in r , the K ad and |Δ G̃ ad 0 | values increase, indicating that the spontaneous tendency of adsorption is enhanced, also similar to the previous reports. …”
Section: Resultssupporting
confidence: 90%
See 1 more Smart Citation
“…With an increase in r , the Γ m increases, while Γ m g decreases, which is consistent with the prediction of our size-effect model. The Γ m values for the four silica samples at pH 9.00 are in the range of 4.18–6.28 μmol/m 2 , similar to the previous reports. Furthermore, with an increase in r , the K ad and |Δ G̃ ad 0 | values increase, indicating that the spontaneous tendency of adsorption is enhanced, also similar to the previous reports. …”
Section: Resultssupporting
confidence: 90%
“…Amorphous silica (SiO 2 ) is one of the most widely used adsorbents. ,,,, Especially, it is suitable for studying the size-dependence of adsorption because it can easily form uniform spherical nanoparticles with adjustable sizes. Cetylpyridinium halide (CPy + X – , commonly X – = Cl – and Br – ) is one kind of quaternary ammoniums surfactant and widely used in various fields ranging from biological to industrial applications. The aggregation behaviors of CPyX in bulk solutions and at solid/liquid interfaces have been widely investigated. However, there have been no reports on the size-dependence of its adsorption at solid/liquid interfaces so far.…”
Section: Introductionmentioning
confidence: 99%
“…CPBr and its chloride analogue (CPCl) have been the subject of several adsorption studies. Harrop 18 found that the adsorption of CPBr was highly dependent on pH, with physisorption predominating at low pH values and chemisorption increasing with pH. Gao et al studied the effect of inorganic salts, alcohols, and urea on the adsorption of CPBr to silica and found that all isotherms exhibited two plateau regions with or without various additives .…”
Section: Introductionmentioning
confidence: 99%
“…Only a handful of studies have dealt with this topic, despite the knowledge that the type of counterion has an important effect on the adsorption of the surfactant . Recently, Favoriti and Treiner ,, have investigated the effect of salicylate counterions on the adsorption of cetylpyridinium onto silica surfaces and on the physical properties of the solloids formed. They observed that salicylate is strongly coadsorbed with cetylpyridinium cations onto silica surfaces and results in a 6-fold increase in the plateau value for adsorption compared to cetylpyridinium chloride.…”
Section: Introductionmentioning
confidence: 99%
“…From analysis of the line widths of the EPR spectra, it was concluded that CPSa on silica surfaces forms two coexisting aggregate phases, one which excludes HTAB* and one in which HTAB* is concentrated. The HTAB* is believed to be excluded from the former phase because of ordering of the salicylate counterion and pyridinium headgroups as proposed by Favoriti and Treiner …”
mentioning
confidence: 96%